Refleksi Nilai-nilai Budaya Lokal Di Balik Praktik Akuntansi Masjid - Thalib, Mohamad Anwar; Suhega, Hilwa Faradhilla; Huruji, Sindriyanti (Institut Agama Islam Negeri Ponorogo, 2023)
Abstract: This study aims to photograph mosque cost accounting based on local wisdom values in Gorontalo. This research topic is important to do because it is an effort to preserve local cultural values from cost accounting practices. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and good deeds. The results showed that the salaries of the worshiper prayer, preacher, caller prayer, and cleaners were taken from the mosque's charity box. The cost of constructing the mosque was obtained from donations from the community, both in the form of building materials and money. In contrast, the cost of providing equipment was taken from the personal funds of the mosque management. The practice of cost accounting is conditional on the value of gratitude (sukuru) and sincerity (ihilasi), which manifest faith in the Creator. In the culture of the people of Gorontalo, these values are often instilled by parents through lumadu